2010
DOI: 10.1001/jama.2010.1843
|View full text |Cite|
|
Sign up to set email alerts
|

Maintaining a High Physical Activity Level Over 20 Years and Weight Gain

Abstract: Context Data supporting physical activity guidelines to prevent long-term weight gain are sparse, particularly during the period when the highest risk of weight gain occurs.Objective To evaluate the relationship between habitual activity levels and changes in body mass index (BMI) and waist circumference over 20 years. Design, Setting, and ParticipantsThe Coronary Artery Risk Development in Young Adults (CARDIA) study is a prospective longitudinal study with 20 years of follow-up, 1985-1986 to 2005-2006. Habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
183
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(201 citation statements)
references
References 38 publications
(52 reference statements)
9
183
3
2
Order By: Relevance
“…Many studies suggest that engaging in high levels of PA for at least 250 minutes per week will help in losing and controlling weight [6][7][8][9]. However, we found that our participants who were trying to lose weight did not engage in sufficient PA that will aid them in losing or controlling their weight.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Many studies suggest that engaging in high levels of PA for at least 250 minutes per week will help in losing and controlling weight [6][7][8][9]. However, we found that our participants who were trying to lose weight did not engage in sufficient PA that will aid them in losing or controlling their weight.…”
Section: Discussioncontrasting
confidence: 59%
“…The benefits of high intensity physical activities in maintaining weight loss is greater among overweight or obese than normal weight individuals [8]. Maintaining high levels of activity are also associated with smaller age-related gains in Body Mass Index (BMI) and waist circumference [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Coronary Artery Risk Development in Young Adults study (CARDIA), a 20-year follow-up prospective longitudinal study with 3,554 men and women, showed that maintaining high levels of activity was associated with smaller gains in WC compared with low activity levels. Men maintaining high activity gained 3.1 fewer centimeters in WC, and women maintaining higher activity gained 3.8 fewer centimeters [104].…”
Section: Physical Activitymentioning
confidence: 95%
“…While biological and genetic factors need to be considered in the regulation of body weight, behavioral adjustments appear to be of particular importance due to the large shift in population weight in a relatively short period of time. Specifically, poor dietary choices and low physical activity (PA) have been suggested as key contributors to excess body weight [17,18]. Even though these correlates of energy balance appear to be the obvious choice for behavioral interventions, not all current recommendations have been backed by scientific data.…”
Section: Limited Success Of Current Intervention Strategiesmentioning
confidence: 99%